التعليم الجامعي المفتوح للبنات دراسة في مزاب بالجزائر - Chikh Salah Salah
This study aims to identify women Open University education in Mzab, Algeria. It also aims to identify the Mzab society of Algeria, which has its own linguistic, sectarian, and social specificities. The researcher employs the descriptive and analytic approaches in carrying out the research as well as using questionnaire as the tool for collecting the data from the individual sample of the entire population. The population encompasses Mzabian female students, their guardians, and the lecturers of its community colleges. The sample consists of 120 students chosen randomly from three different community colleges in Mzab and others. The study is made up of 44 paragraphs, which consist of three pivotal ideas as thus: improving women Open University education in Mzab, collecting data from students, lecturers, and guardians. The data obtained through the questionnaire is then analyzed using frequency table, percentage, median and standard deviation. The contrast is analyzed through the statistical package for the social sciences called SPSS which facilitates the coming up of the researcher with the following findings: Manifestation of approval among students regarding the improvement of the women open university education in Mzab, the approval which supports the study and emphasizes on the necessity of establishing an open university for the women of Mzab. Manifestation of approval among lecturers as regards the improvement of women Open University education in Mzab even though the approval is not absolute due to their experience on modern higher education. And the effectiveness of the agreement of the guardians as regards improvement of women open university education in Mzab inclines towards making it similar to public and community universities. Lastly, the research makes the following recommendations: The necessity of considering the status of women in the society as complementary to men and not properties they possess. Giving them freedom to study in any fields of their choice provided that the course chosen is not contradictory to the religion and femininity. The necessity of taking a quick step towards reforming women education at all levels in the community to ensure its correspondence with the global educational standards.